Pengaruh Etika Kepemimpinan, Fungsi Badan Pengawas dan Pengalam Kerja Terhadap Kualitas laporan Keuangan - Ni Putu Lilik Karmila Dewi; I Putu Deddy Samtika Putra (UNHI Press, 2022)
The researcher conducted an observation to see the influence between the ethics of the leader, the function of the internal supervisory body, and work experience on the quality of financial reports in LPD, Mengwi District, Badung Regency. LPD employees who act as presenters of financial statements from 38 LPDs that have met the criteria are used as the population in this study. The results of this study indicate that the quality of financial reports at the LPD of Mengwi Badung Regency can be influenced by three independent variables. This research can later be used as a reference and contribution of ideas in the process of drafting policy regulations related to financial reports at the LPD of Mengwi Badung Regency.